Impacts of the IUCN Red List of Ecosystems on conservation policy and practice. Issue 5 (24th July 2019) - Bland, Lucie M.; Nicholson, Emily; Miller, Rebecca M.; Andrade, Angela; Carré, Aurélien; Etter, Andres; Ferrer‐Paris, José Rafael; Herrera, Bernal; Kontula, Tytti; Lindgaard, Arild; Pliscoff, Patricio; Skowno, Andrew; et al.
Abstract: In 2014, the International Union for Conservation of Nature adopted the Red List of Ecosystems (RLE) criteria as the global standard for assessing risks to terrestrial, marine, and freshwater ecosystems. Five years on, it is timely to ask what impact this new initiative has had on ecosystem management and conservation. In this policy perspective, we use an impact evaluation framework to distinguish the outputs, outcomes, and impacts of the RLE since its inception. To date, 2, 821 ecosystems in 100 countries have been assessed following the RLE protocol. Systematic assessments are complete or underway in 21 countries and two continental regions (the Americas and Europe). Countries with established ecosystem policy infrastructure have already used the RLE to inform legislation, land‐use planning, protected area management, monitoring and reporting, and ecosystem management. Impacts are still emerging due to varying pace and commitment to implementation across different countries. In the future, RLE indices based on systematic assessments have high potential to inform global biodiversity reporting. Expanding the coverage of RLE assessments, building capacity and political will to undertake them, and establishing stronger policy instruments to manage red‐listed ecosystems will be key to maximizing conservation impacts over the coming decades.